Food business food safety inspections scoring, rating and disclosure systems— engaging consumers in foodborne disease control: A systematic review and research agenda for low- and middle-income countries - Dinede, Getachew; Makau, D.; Duvenage, S.; Amenu, Kebede; Grace, Delia (International Livestock Research Institute, 2024)
Key messages Food inspection is not effective in low- and middle-income countries and innovative approaches are needed to motivate greater compliance with standards. ‘Scores on doors’ could motivate greater compliance through the power of public demand and opinion. This systematic literature review found no studies investigating food inspection programs in low- and middle-income countries. While studies from high-income countries show wide variation of hygiene factors considered; their weight, and scoring; and requirement for disclosure. More evidence is needed on optimizing ‘scores on doors’ in high-income countries and application to low- and middle-income countries.